Validitas E-Modul Fisika Terintegrasi Materi Bencana Petir Berbasis Experiential Learning - Fadieny, Nurul; Fauzi, Ahmad (Universitas Negeri Padang, 2021)
Physics is a part of science that relating to natural phenomena. Physics learning must be integrated with natural phenomena material, one of which is lightning. Lightning material is integrated in physics learning using teaching material, namely e-module based on experiential learning models. E-module which is feasible to be used in learning is a valid e-module.A research aim to obtain validity of physics e-module integrated by lightning disaster material based on experiential learning. The method of this research was descriptive study. The validity of e-module can be measured using instrument in the form of a validation questionnarie. Validation component consists of the feasibility of contents, presentation feasibility, linguistic eligibility, and graphic feasibility. Validity of e-module was assessed by experts and practitioners. Based on the results of validation of experts and practitioners, physics e-module integrated by lightning disaster material based on experiential learning has been proven valid and worthy of being tested in learning.